OTİZM GENETİĞİ - YÜKSEL, Adnan (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Autism is a complex neurodevelopmental disorder. Etiology has not been clearly noticed up to date. Although some types of autism are hereditary on their own or as part of genetic syndrome, the others emerge from environmental factors Family and twin studies have shown that genetic factors are significant in the disease’s etiology. The disease was noticed to show both locus and allelic heterogeneity. The researches offered the most evidence for combined many additive genes and environmental factors in absence of major gene effect. This suggested a multifactorial threshold model. Today various studies (chromosome anomalies, genetic linkage analysis, assosiation studies) on autism are being done to notice the sensitive genes. Up to date a number of both structural and numerial chromosome anomalies have been reported. Due to the fact that patient selection criteria were different, different genetic markers were used and map and statistic analysis were changeable, the results varied. Neverthless maximum Lod score in 2, 3, 7, 11, 15, 17 and X chromosomes was found significant. Intensive studies are done on following genes, GAT1 and OXTR on chromosome 3, FOXP2,WNT2,RELN,HOXA1 and HOXB1 on chromosome 7, HRAS on chromosome 11, GABRB3, GABRA5, GABRG3, UBE3A and ATP10C on chromosome 15, 5-HTT on chromosome 17, MeCP2, NLGN3 and NLG4 on chromosome X.